Stages of the 2007/2008 Global Financial Crisis Is There a Wandering Asset-Price Bubble? - Lucjan T. Orlowski (Kiel Institute for the World Economy (IfW), 2008)
This study identifies five distinctive stages of the current global financial crisis: the meltdown of the subprime mortgage market; spillovers into broader credit market; the liquidity crisis epitomized by the fallout of Northern Rock, Bear Stearns and Lehman Brothers with counterparty risk effects on other financial institutions; the commodity price bubble, and the ultimate demise of investment banking in the U.S. The study argues that the severity of the crisis is influenced strongly by changeable allocations of global savings coupled with excessive credit creation, which lead to over-pricing of varied types of assets. The study calls such process a 'wandering asset-price bubble'. Unstable allocations elevate market, credit and liquidity risks. Monetary policy responses aimed at stabilizing financial markets are proposed.
Keywords: G24; G12; G15; G21; 330; Subprime mortgage crisis; credit crisis; liquidity crisis; market risk; credit risk; default risk; counterparty risk; Basel II; Finanzmarktkrise; Vermögen; Bubbles; Spillover-Effekt; Ansteckungseffekt; Hypothek; Kreditmarkt; Geldmarkt; Kreditwürdigkeit; Bankenaufsicht; Welt